PEDAGOGIA ÎNVĂŢĂRII INDIVIDUALE ÎN CADRUL UNIVERSITAR - USM ADMIN (Moldova State University, 2007)
The pedagogy of individual learning at the university, studying/individual activity represents a modality of organization of a correlation "subject-subject", on the level of educational, the objectives of research activities being realized by the students independently, with or without the help of the teachers. The individual activity realized personally offers different/common themes adapted to the particularities, necessities and interests of the student, but also to the curricula objectives.